End-capped Polyamide 12: Impact of Powder Bed Fusion-Induced Aging Mechanisms - Neitzel, Fabian; Nölle, Florian; Kletetzka, Ivo; Schmid, Hans-Joachim (Additive Manufacturing Letters)

Zur Relativität islamischer Normativität: Diskurslinien der taṣwīb-Lehre von al-Ǧāḥiẓ (gest. 869) zu al-Ǧaṣṣāṣ (gest. 981) und al-Baṣrī (gest. 1044) - Abdelrahem, Mohammed (Forum Islamic-Theological Studies)
This article explores the relativity of Islamic normativity through the taṣwīb doctrine (kullu mujtahid muṣīb) as formulated by al-ʿAnbarī and received by al-Jāḥiẓ (d. 255/869), al-Jaṣṣāṣ (d. 370/981), and al-Baṣrī (d. 436/1044). Al-Jaṣṣāṣ reinterprets the thesis through the ḥanafī principle of ashbah bi-l-aṣl as a hermeneutical-methodological approach; al-Baṣrī elaborates it into an epistemo-logical model of normative plurality, while al-Jāḥiẓ articulates a soteriological theory of moral responsibility in the context of kalām. The analysis shows that classical Islamic legal theory developed a distinct modelof normativity that maintains binding force under conditions of pluralism and uncertainty. The article calls for renewed engagement with this tradition in contemporary debates on religious normativity and legal pluralism.
Keywords: IslamicTheology; Usul al-Fiqh; taswib; islamische Rechtsphilosophie; LegalTheory; Pluralism; OpenAccess

Measurement of multiphysical material parameters of piezoceramic components for high-power ultrasonic applications - Friesen, Olga; Claes, Leander; Hölscher, Jonas; Henning, Bernd; Scheidemann, Claus; Hemsel, Tobias; Kuess, Raphael; Walther, Andrea; Spieker, Carsten; Förstner, Jens (tm - Technisches Messen)
Simulation-based design of high-power ultrasonic systems depends on the accurate modelling of the electromechanical behaviour of piezoceramic materials. In practical transducer applications, the relevant operating points are influenced by mechanical preload and heating, both of which give rise to changes in the elastic, dielectric, and piezoelectric material properties. Material parameters identified under idealised, unloaded conditions are therefore insufficient to represent piezoceramic material behaviour under realistic operating conditions. To overcome this limitation, experimental setups are developed that enable the measurement of electrical impedance spectra under controlled thermal and mechanical conditions. The acquired impedance data are used in an inverse identification procedure, in which the behaviour of a finite element forward model is iteratively fitted to the measurements using a block coordinate descent optimisation strategy guided by a sensitivity analysis. This yields effective linear material parameters as a function of temperature and mechanical stress at varying operating points. The identified temperature-dependent parameters, for instance, can be employed in a coupled thermo-electromechanical simulation framework to predict the temperature-dependent material behaviour during operation. The linear identification based on varying operation points provides an initial approximation of the nonlinear material response, establishing a basis for the development of corresponding nonlinear material models.
Keywords: tet_topic_piezo

A verification-stability-validation framework for optimal hyperelastic modeling of rubber-like materials - Houari, Fadoua; Caylak, Ismail; Ostwald, Richard (Mechanics of Materials)

Modellierung und Simulation des temperaturabhängigen Materialverhaltens von Piezokeramiken mit FEniCS - Spieker, Carsten; Kuess, Raphael; Walther, Andrea; Förstner, Jens (Fortschritte der Akustik - DAGA 2026)
Keywords: tet_topic_piezo

A Step Towards Inherently Interpretable Causal Machine Learning Models For Decision Support - Zapata Gonzalez, David Ricardo (ECIS Conference)

Experimental investigation of local joining element kinematics in mechanical joints and surrogate modelling for crash applications - Bähr, Philipp; Striewe, Marius; Dargel, Alrik; Sommer, Silke; Hein, David; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
Subject of this paper is the investigation of the influence of local joint kinematics on the load-bearing and failure behavior of self- piercing riveted (SPR) joints. It can be shown that the local joint kinematics of SPR joints correlate with the failure mechanism of the joint. The kinematics are highly influenced by the material properties of the joining partners. Detailed experimental results from tensile tests on a representative SPR joint are presented, with local joint kinematics quantified using multiple complementary measurement methods (optical measurement, micrographs, in situ computer tomography). Furthermore, results of component tests are shown where the kinematics of the joints have been measured in the same manner. The experimental results are later used to calibrate simulation models for crash application which are used to simulate the specimen and component tests. The results of the investigation show that the local joint kinematic influences the failure behavior of the joint. Simulations of the experimental tests have shown good results, and the investigated models are able to predict the actual joint behavior.

Education as a Moderator of Genetic Mortality Risk - Schmitz, Hendrik; Nguyen, Thao Le

Predicting Heterogeneous Treatment Effects Of Building Energy Saving Retrofits Using Causal Machine Learning - Zalipski, Kevin; Zapata Gonzalez, David Ricardo; Müller, Oliver

DiSerHub Startet in die zweite Phase – Digitale Transformation für die Automobilindustrie - Kundisch, Dennis

Metadata Model for Engineering of Sustainable Products in Value Creation Networks - Gräßler, Iris; Rarbach, Sven; Pottebaum, Jens; Luessen, Florian; Hoffmann, Joerg (Procedia CIRP)

Metadata-based assessment of Data Quality for Engineering of Sustainable Products - Gräßler, Iris; Rarbach, Sven; Pottebaum, Jens; Hoffmann, Joerg (Procedia CIRP)

Atmospheric Corrosion Protection of LPBF Manufactured AlSi10Mg by Combining SiO x ‐CVD and PDMS Grafting - Prüßner, Tim; Hoyer, Kay-Peter; Buitkamp, Nadine; Grundmeier, Guido (Materials and Corrosion)
ABSTRACT Additive manufacturing by laser powder bed fusion enables complex AlSi10Mg components but produces a heterogeneous microstructure prone to localized corrosion. In this study, hydrophobic polydimethylsiloxane (PDMS) ultrathin films, with and without an SiO ₓ interlayer attached by chemical vapor deposition (CVD), were applied for corrosion mitigation. Surface modifications were characterized by X‐ray photoelectron spectroscopy (XPS), polarization modulation–infrared reflection–absorption spectroscopy (PM‐IRRAS) and water contact angle (WCA) measurements. Electrochemical behavior was evaluated by electrochemical impedance spectroscopy (EIS), linear sweep voltammetry (LSV), and chronoamperometry by a droplet‐cell approach. Atmospheric corrosion processes simulating marine corrosion were monitored by optical microscopy. Spectroscopic analyses confirm successful PDMS attachment. Electrochemical measurements reveal reduced corrosion current densities by one magnitude, suppressed pitting activity, and anodic shifts of the pitting potential. The SiO ₓ ‐CVD + PDMS bilayer exhibits the highest resistance to atmospheric corrosion.

AI-Based Enterprise Architecture Management in Engineering Domain: A Systematic Literature Review - Kürpick, Dominik; Hovemann, Aschot; Kürpick, Christian; Gabriel, Stefan; Lick, Jonas; Dumitrescu, Roman (2025 International Conference on Intelligent & Innovative Practices in Engineering & Management (IIPEM))

Bridging Academic and Vocational Knowledge: Professionalization in Vocational Teacher Education - Sänger, Niklas

Digitale Teilhabe in der Sprachtherapie: Perspektiven aus der Praxis Ergebnisse einer quantitativen Fragebogenerhebung - Thorndahl, Dennis; Rosenkranz, Anna; Jonas, Kristina (Logos)

„transMINT4.0“ – MINT-Bildung stärken durch die Ein- bindung außerschulischer Lernorte am Übergang von der Primar- zur Sekundarstufe - Blumberg, Eva; Wenzel, Annkathrin; Schulze, Jan Roland; Reckmann, Eileen; Puppe, Ricardo; Crummenerl, Lena Luise; Temmen, Katrin (GDSU-Journal)

Neue Perspektiven auf digitalisierungsbezogene MINT-Lehrkräftefortbildungen für den Sachunterricht im Kontext von Schülerlaboren. - Blumberg, Eva; Crummenerl, Lena Luise; Lüsse, Mientje; Brückmann, Maja; Wassing, Janne Lene; Acher, Andres; Sowinski, Ronja; Abels, Simone (Perspektiv(en)wechsel – Sachunterricht neu denken)

Fundamental Patterns – A Taxonomy for Archetype Development in Information Systems - Koldewey, Christian; Avermeyer, Celina Maleen; van der Valk, Hendrik; Zerbin, Julian; Dumitrescu, Roman (Lecture Notes in Computer Science)

Systematic Approach to Early Validation Based on the System Architecture of Advanced Systems in the B2B Sector - Humpert, Lynn; Disselkamp, Jan-Philipp; Cichon, Gerrit; Anacker, Harald; Dumitrescu, Roman (IEEE Engineering Management Review)